PERANCANGAN PENGENDALIAN PERSEDIAAN BAHAN BAKU PLYWOOD FALCATA DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) (Studi Kasus PT. Prima Parquet Indonesia Cabang Sukoharjo) - Ardiyansah, Reza; Dicasani, Alifta; Betanursanti, Ida; Widyastuti, Widyastuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
PT Prima Parquet Indonesia is a manufacturing company engaged in wood processing, particularly in the production of Falcata Plywood. The company faces challenges in managing raw material inventory, such as procurement delays, overstock, and material shortages, which can disrupt the production process and increase operational costs. This study aims to design a raw material planning and inventory control system using the Material Requirement Planning (MRP) method to ensure the availability of raw materials in a timely, efficient, and production-oriented manner. The research stages include developing a Master Production Schedule (MPS), creating a Bill of Material (BOM), collecting lead time data, and calculating net requirements using the lot sizing technique. The results show that the implementation of the MRP method, particularly with the Lot for Lot (LFL) technique, is more optimal than the company’s conventional method because it can reduce inventory costs and prevent both shortages and excesses of raw materials. The application of the MRP system also improves operational efficiency, supports structured production planning, and ensures smoother production processes at PT Prima Parquet Indonesia. Therefore, the MRP method can serve as a strategic solution for raw material inventory control in the wood processing industry.